Significance of progressive liver fibrosis in pediatric liver transplants: A review of current evidence - George, Mathew (World J Gastroenterol, 2020)
This article reviews the current evidence and knowledge of progressive liver fibrosis after pediatric liver transplantation. This often-silent histologic finding is common in long-term survivors and may lead to allograft dysfunction in advanced stages. Surveillance through protocolized liver allograft biopsy remains the gold standard for diagnosis, and recent evidence suggests that chronic inflammation precedes fibrosis.